Escalating and De-escalating Temporary Mechanical Circulatory Support in Cardiogenic Shock: A Scientific Statement From the American Heart Association. Issue 6 (7th July 2022) - Geller, Bram J.; Sinha, Shashank S.; Kapur, Navin K.; Bakitas, Marie; Balsam, Leora B.; Chikwe, Joanna; Klein, Deborah G.; Kochar, Ajar; Masri, Sofia C.; Sims, Daniel B.; Wong, Graham C.; Katz, Jason N.; et al.
Abstract : The use of temporary mechanical circulatory support in cardiogenic shock has increased dramatically despite a lack of randomized controlled trials or evidence guiding clinical decision-making. Recommendations from professional societies on temporary mechanical circulatory support escalation and de-escalation are limited. This scientific statement provides pragmatic suggestions on temporary mechanical circulatory support device selection, escalation, and weaning strategies in patients with common cardiogenic shock causes such as acute decompensated heart failure and acute myocardial infarction. The goal of this scientific statement is to serve as a resource for clinicians making temporary mechanical circulatory support management decisions and to propose standardized approaches for their use until more robust randomized clinical data are available.